A novel non-enzymatic sensing platform for determination of 5′-guanosine monophosphate in meat. (15th July 2019) - Fei, Qiqi; Zhang, Nana; Sun, Chong; Zhang, Panpan; Yang, Xiaodi; Hua, Yunhui; Li, Li
Highlights: g-C3 N4 doped carboxylated MWCNTs nanocomposite was synthesized using a simple method. A simple non-enzymatic GMP sensor was prepared and investigated. The sensor was used to detect the concentration of GMP with a satisfactory result. Abstract: Graphitic carbon nitride (g-C3 N4 ) doped carboxylated MWCNTs nanocomposite was synthesized using a simple method. The composite films containing 45 wt%, 50 wt%, 56 wt%, 67 wt% fraction of the carboxylated MWCNTs doped into g-C3 N4 were fabricated and characterized. An electrochemical non-enzymatic sensor for determination of 5′-guanosine monophosphate (GMP) based on the nanocomposite was developed. The results indicate that the g-C3 N4 -carboxylated MWCNTs nanocomposite has highly electrocatalytic activity, good conductivity and biocompatibility, which plays an essential role in the determination of GMP. Under the optimum conditions, the linear fitting equation was I (µA) = −0.0022c (μg·mL −1 ) + 0.3560 (R 2  = 0.9982). The linear range was from 0.5 to 100 μg·mL −1 and the detection limit (LOD, S/N = 3) was 0.109 μg·mL −1 . This non-enzymatic sensor can offer a better alternative to other methods for the analysis of GMP because of cheap cost, low detection limit and good anti-jamming capability in meat quality evaluation.